Roles of Stromal Cell RANKL, OPG, and M-CSF Expression in Biphasic TGF-β Regulation of Osteoclast Differentiation - KARST, MARY (J Cell Physiol, 2004)
To better understand the complex roles of transforming growth factor-beta (TGF-β) in bone metabolism, we examined the impact of a range of TGF-β concentrations on osteoclast differentiation. In co-cultures of support cells and spleen or marrow osteoclast precursors, low TGF-β concentrations stimulated while high concentrations inhibited differentiation. We investigated the influences of TGF-β on macrophage colony stimulating factor (M-CSF), receptor activator of NF-κB ligand (RANKL), and osteoprotegerin (OPG) expression and found a dose dependent inhibition of M-CSF expression. RANKL expression was elevated at low TGF-β concentrations with a less dramatic increase in OPG. Addition of OPG blocked differentiation at the stimulatory TGF-β dose. Thus, low TGF-β concentrations elevated the RANKL/OPG ratio while high concentrations did not, supporting that, at low TGF-β concentrations, there is sufficient M-CSF and a high RANKL/OPG ratio to stimulate differentiation. At high TGF-β concentrations, the RANKL/OPG ratio and M-CSF expression were both repressed and there was no differentiation. We examined whether TGF-β-mediated repression of osteoclasts differentiation is due to these changes by adding M-CSF and/or RANKL and did not observe any impact on differentiation repression. We studied direct TGF-βimpacts on osteoclast precursors by culturing spleen or marrow cells with M-CSF and RANKL. TGF-β treatment dose-dependently stimulated osteoclast differentiation. These data indicate that low TGF-β levels stimulate osteoclast differentiation by impacting the RANKL/OPG ratio while high TGF-β levels repress osteoclast differentiation by multiple avenues including mechanisms independent of the RANKL/OPG ratio or M-CSF expression regulation.